OVEREXPRESSION VASCULAR ENDOTHELIAL GROWTH FACTOR IN NASOPHARYNGEAL CARCINOMA WITH UNDIFFERENTIATED CARCINOMA TYPE IN ADVANCED STAGE - Kadek Kris Aryana (TALENTA PUBLISHER, 2019)
Introduction: Nasopharyngeal Carcinoma (NPC) is a malignancy that tends to diagnosed at an advanced stage with low survival and prognosis rate. One of the factors that may play a role in progressivity and metastasis of tumor is overexpression of vascular endothelial growth factor (VEGF), which is a key role in tumor angiogenesis. Objective: This study aims to learn the expression of VEGF in NPC with Undifferentiated Carcinoma type and to learn the association pf VEGF Expression with tumor stage of NPC Method: This is a cross-sectional study performed in ENT-HNS Department of ENT-HNS of Udayana University/Sanglah Hospital. The sample was collected by consecutive nonprobability sampling, starting from January 2016. NPC patients underwent Histopathologic examination from a nasopharyngeal biopsy. The result is Undifferentiated Carcinoma. VEGF expression analyzed by red-brown stained cytoplasm. Data were analyzed by Spearman's Correlation Test Chi-Square test, and Paired Sample t-Test. Result: VEGF positive Expression was found in 27 of 28 (96.4%) Undifferentiated Carcinoma type of NPC cases. VEGF overexpression was found in 23 of 28 (82.4%) Undifferentiated Carcinoma type of NPC cases.There is significant correlation found between tumor stage and VEGF expression (p<0.05). Conclusion: From the research, it could conclude that there is significant correlation between tumor stage and VEGF Expression.